When Brand Logos Describe the Environment: Design Instability and the Utility of Safety-Oriented Products. Issue 3 (8th July 2016) - Rahinel, Ryan; Nelson, Noelle M.
Abstract : A core assumption underlying brand logo design is that inferences generated from a logo's design are applied to the consideration target (e.g., product or brand) to which the logo is attached, and designs should therefore reflect the beliefs one wishes to promote about the target. The current work demonstrates an important case in which consideration targets are resistant to particular inferences, which leads such inferences to be applied instead to one's environment. Specifically, when considering safety-oriented products, consumers exposed to unstable-looking brand logos infer the presence of unsafe conditions, and because safety-oriented products are resistant to inferences that they are unsafe, the inference is instead applied to the environment (i.e., "the environment is unsafe"). This process subsequently increases the perceived utility of safety-oriented products. Five experiments collectively demonstrate the core effect, uncover the underlying inferential mechanism, and demonstrate the crucial role of inference resistance in the process. Overall, the present findings suggest that in some cases, a logo design that is opposed to desired product or brand beliefs may ironically help in boosting demand.